2020
DOI: 10.3389/fped.2020.00505
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Parental Satisfaction With Early Discharge of Preterm Infants on Nasogastric Tube Feeding and Outpatient Clinic Follow-Up

Abstract: Aim: To evaluate our early discharge program of preterm infants with nasogastric tube feeding (NTF) and close outpatient clinic follow-up with regard to safety, parent satisfaction and parental stress level. Methods: 119 preterm infants were discharged on NTF from our tertiary care neonatal unit (median gestational age 31.0 weeks, median birthweight 1,650 g). Parental satisfaction was evaluated by a standardized questionnaire. For safety assessment growth until term equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[2][3][4] Home nasogastric (HNG) tube feeding programs have shown high parental satisfaction and increased familial bonding without deprivation of an authentic biological environment. 5 HNG programs were developed to assist infants in their feeding development outside of the hospital environment. Studies have shown the safety and utilization of HNG programs not only for pre-term infants, but also for medically complex infants as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Home nasogastric (HNG) tube feeding programs have shown high parental satisfaction and increased familial bonding without deprivation of an authentic biological environment. 5 HNG programs were developed to assist infants in their feeding development outside of the hospital environment. Studies have shown the safety and utilization of HNG programs not only for pre-term infants, but also for medically complex infants as well.…”
Section: Introductionmentioning
confidence: 99%
“…Parental satisfaction with a HNG program is very high since many experienced lower stress levels, had better child and caregiver attachment, and were likely to recommend the program to other parents. 5,7 Families also have the ability to attempt oral feeding at home before making the decision to undergo a procedure which could result in an additional hospital stay. Avoidance of prolonged NICU admission and additional hospitalizations decreases the risk of iatrogenic harm and costs for families and hospital systems.…”
Section: Introductionmentioning
confidence: 99%
“…A small pilot early discharge programme demonstrated a reduction in length of stay of 10.6 days and cost savings of US$7674/patient 11. Beyond cost, early discharge programmes are also associated with high-satisfaction and preparedness, and positive quality indicators (eg, growth and readmissions) 12. Prior research highlights potential savings, but also recognises a need for strategies to monitor and mitigate health risks of earlier discharge 13…”
Section: Introductionmentioning
confidence: 99%
“…For example, safety and parental satisfaction with early discharge of preterm infants on nasogastric tube feeding and outpatient clinic follow-up was evaluated. 24 One hundred and nineteen preterm infants were discharged on nasogastric tube feeding from a tertiary care neonatal unit. Parental satisfaction was evaluated by a standardized questionnaire.…”
mentioning
confidence: 99%